Longitudinal changes in dopamine transporter uptake scans in progressive apraxia of speech - Rene L. Utianski; Nha Trang Thu Pham; Hugo Botha; Farwa Ali; Joseph R. Duffy; Heather M. Clark; Val J. Lowe; Jennifer L. Whitwell; Keith A. Josephs (Clinical Parkinsonism & Related Disorders, 2023)
Purpose: To describe qualitative and quantitative longitudinal changes in dopamine transporter uptake (DaT) scan findings in progressive apraxia of speech (PAOS) patients. Methods: DaTQUANT software was used to quantify uptake in the left and right caudate and putamen in DaT scans of 39 patients with PAOS, 19 with repeat scans. Clinical radiologic impressions were used as the gold standard for evaluating whether quantitative measures (z-score of left and right putamen and caudate uptake) aligned with gestalt impressions of DaT abnormalities and clinical impairments, cross-sectionally. Measures at first and last available DaT were used to evaluate change over time and the influence of qualitative abnormality at first visit on change over time. Results: Cross-sectionally, 16/39 patients had abnormal DaT scans on visual read, with differences in all quantitative DaT measures between those with (ab)normal scans, but without differences in any clinical measures (apraxia of speech, aphasia, or parkinsonism). Three patients that had normal DaT scans at baseline were read as abnormal at subsequent visits, with coinciding change in quantitative measures. At the group level, across the 19 patients with repeat imaging, no statistical change in left or right caudate or putamen scores was observed despite progression of clinical indices. Abnormality at first visit did not statistically influence the rate of change over time, although trends were observed. Conclusions: Approximately 40–50% of patients with PAOS have or will develop DaT scans that may be visually read as abnormal. Quantitative measures of DaT match visual reads cross-sectionally, but may not map to clinical progression, including of parkinsonism, observed in these patients.